1985
DOI: 10.1111/j.1600-0447.1985.tb02597.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric effects of cannabis use

Abstract: That cannabis use may provoke mental disturbances is well known to Scandinavian psychiatrists today. A review of the psychiatric aspects of cannabis use is given, and the clinical signs of 70 cases of cannabis psychoses collected in Sweden are described. The bluntness and "amotivation" following chronic cannabis use are discussed. Anxiety reactions, flashbacks, dysphoric reactions and an abstinence syndrome are all sequels of cannabis use. Three risk groups begin to emerge: a) Young teenage cannabis users who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 30 publications
4
33
0
1
Order By: Relevance
“…The cannabis psychosis cases differed from the control subjects in several important ways: they had less precipitating factors other than cannabis use itself, their affect was more reactive and congruent with their thinking; schizophrenic formal thought disorder was conspicuous by its absence -a feature consistently noted earlier [6][7][8] though not always [3]; less of them had hallucinations, but when present, the hallucinations would occur more typically in multiple modalities, again consistent with some previous studies [6][7][8], but not all [3]; other perceptual abnormalities were also commoner; more of them had multiple delusions, and some showed elated mood [noted earlier, [6][7][8][9]. Their course and outcome also showed striking and characteristic differences in duration of index episode and association with cannabis in having a relapse.…”
Section: Discussionsupporting
confidence: 77%
“…The cannabis psychosis cases differed from the control subjects in several important ways: they had less precipitating factors other than cannabis use itself, their affect was more reactive and congruent with their thinking; schizophrenic formal thought disorder was conspicuous by its absence -a feature consistently noted earlier [6][7][8] though not always [3]; less of them had hallucinations, but when present, the hallucinations would occur more typically in multiple modalities, again consistent with some previous studies [6][7][8], but not all [3]; other perceptual abnormalities were also commoner; more of them had multiple delusions, and some showed elated mood [noted earlier, [6][7][8][9]. Their course and outcome also showed striking and characteristic differences in duration of index episode and association with cannabis in having a relapse.…”
Section: Discussionsupporting
confidence: 77%
“…18 Second, we excluded subjects using cannabis who were acutely intoxicated or going through cannabis withdrawal symptoms, variables that may influence cognition in healthy subjects. 19 Acute cannabis intoxication is more clearly associated with cognitive dysfunction, 20 emotional changes, 21 and an Cannabis . noncannabis; p , 0.05, cluster size $500.…”
Section: E14mentioning
confidence: 99%
“…One facet of scientifi c attention in the study of marijuana has been devoted to understanding whether frequent (e.g., daily, weekly) marijuana use may increase an individual's vulnerability for developing and maintaining depressive and anxiety symptoms and disorders (Chen et al, 2002;Green and Ritter, 2000;Thomas, 1996;Tunving, 1985;Zvolensky et al, 2006b). Interestingly, research within this area has been equivocal.…”
mentioning
confidence: 99%
“…For example, although marijuana use has been related to an increased risk of depressive symptoms and disorders (Chen et al, 2002;Hall and Solowij, 1998), the majority of such empirical work indicates that the strength of such associations is markedly attenuated, and often nonexistent, after controlling for demographic variables such as gender (Brook et al, 2001;Degenhardt et al, 2001). In terms of anxiety and its disorders, relatively more consistent relations have been evident between frequent or more severe marijuana-use problems (e.g., marijuana dependence) and panic psychopathology (Hollister, 1986;Thomas, 1996;Tunving, 1985). For example, Hathaway (2003) found that among weekly users of marijuana (N = 140), approximately 40% reported having had at least one panic attack related to such use.…”
mentioning
confidence: 99%